Evaluasi Subjektif Teknik Perekaman Stereo Pada Kendang Jawa - Jack Arthur Simanjuntak; Gelar Pandu Raharjo (Institut Seni Indonesia Denpasar, 2022)
Kendang Jawa is a traditional Javanese musical instrument which is used in a Javanese gamelan ensemble, often played for traditional events. Kendang Jawa has three separate parts dependant on its size, namely bem (largest), batangan (medium) and ketipung (small). Through advances in recording technology, the development and preservation of Nusantara's musical arts can continue to be encouraged. The quality of the recording is predominantly determined by the placement of the microphone in use. The lack of studies on the importance of microphone layouts and distancing in kendang Jawa recording is a problem that requires attention. The purpose of this study is to evaluate the participants' subjective assessment of stereo recording techniques on kendang Jawa. Qualitative methods were used to analyze the preferences of expert and non-expert participants. Recording of 16 audio samples were performed using four stereo recording techniques, namely XY 90º, AB, ORTF and Mid-Side with four variable distances at Studio Lokananta, Surakarta. The recording sample was tested subjectively on 40 participants. This study reveals that the preference of expert and non-expert participants is the XY 90º technique. As many as 73% of expert participants enjoyed the recording of kendang Jawa through the XY 90º technique at a distance of 1 meter. High sound clarity and balanced stereo images are several crucial factors in this technique. The result of this study contributes to the understanding that the aspect of the impression of space and time of low reverberation is one of the essential criteria in determining the sound quality of kendang Jawa recordings.